Seroprevalence of respiratory viral pathogens of indigenous calves in western Kenya - Callaby, R.; Toye, Philip G.; Jennings, A.; Thumbi, Samuel M.; Wyk, Ilana Conradie van; Hanotte, Olivier H.; Mbole-Kariuki, Mary N.; Bronsvoort, B.M. de C.; Kruuk, L.E.B.; Woolhouse, Mark E.J.; Kiara, Henry K. (Elsevier, 2016)
Most studies of infectious diseases in East African cattle have concentrated on gastro-intestinal parasites and vector-borne diseases. As a result, relatively little is known about viral diseases, except for those that are clinically symptomatic or which affect international trade such as foot and mouth disease, bluetongue and epizootic haemorrhagic disease. Here, we investigate the seroprevalence, distribution and relationship between the viruses involved in respiratory disease, infectious bovine rhinotracheitis virus (IBR), bovine parainfluenza virus Type 3 (PIV3) and bovine viral diarrhoea virus (BVDV) in East African Shorthorn Zebu calves. These viruses contribute to the bovine respiratory disease complex (BRD) which is responsible for major economic losses in cattle from intensive farming systems as a result of pneumonia. We found that calves experience similar risks of infection for IBR, PIV3, and BVDV with a seroprevalence of 20.9%, 20.1% and 19.8% respectively. We confirm that positive associations exist between IBR, PIV3 and BVDV; being seropositive for any one of these three viruses means that an individual is more likely to be seropositive for the other two viruses than expected by chance.